Protein Expression of PTTG-1, OCT-4, and KLF-4 in Seminoma: A Pilot Study - Grande, Giuseppe; Milardi, Domenico; Martini, Maurizio; Cenci, Tonia; Gulino, Gaetano; Mancini, Francesca; Bianchi, Antonio; Pontecorvi, Alfredo; Pierconti, Francesco (Frontiers in Endocrinology, 2019)
Seminomas are the most frequent kind of testicular germ cell tumors (TGCTs), accounting for 50% of tumor diagnosis in young men, whereas non-seminomas account for 40% and mixed forms for 10% of cases. It is currently supposed that TGCTs evolve from a pre-invasive stage of carcinoma in situ (CIS). Octamer-binding transcription factor 4 (OCT4) is essential for self-renewal of stem cells. It is considered as a major regulator of cell pluripotency. Prior studies have shown that seminoma expresses OCT4. Transcription factor Krüppel-like factor 4 (KLF4) has moreover associated with embryonic stem cell maintenance. Finally, we previously demonstrated the expression of PTTG1 in CIS and seminomas. In this pilot study, we compared the combined expression of PTTG1 with KLF4 and OCT4 in seminoma, in order to validate our hypotesis that PTTG1 marks a specific population of stem cells in neoplastic tissue, strictly related with tumor. Formalin-fixed and paraffin-embedded testicular tissues by 5 patients who underwent an orchidectomy for seminoma have been collected and immunofluorescence analysis was performed using antibody rabbit monoclonal PTTG-1 and mouse monoclonal OCT4 or mouse monoclonal KLF4 antibody. In seminoma we observed that tumor cells strongly express OCT-4 in all seminomas and in the intratubular areas of seminoma. Expression of KLF-4 was observed in many tumor cells. PTTG1 marks some specific OCT4- and KLF4-positive tumor cells, mainly localized at the periphery of the neoplasm. In the intertubular infiltration areas nests of cells expressing both OCT4/KLF4 and PTTG1 have been observed. This is the first identification of a cell population in seminoma characterized for being OCT4, KLF4, and PTTG1 positive cells in seminoma, associated with cancer invasiveness. Further investigation is needed to elucidate if a functional abrogation of PTTG1 might be used in order to offer new therapeutic approaches in the clinical workout of seminoma.